2004
DOI: 10.1099/mic.0.27381-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Myxococcus xanthus mutant that is defective for adventurous motility and social motility

Abstract: Myxococcus xanthus is a gliding bacterium that possesses two motility systems, the adventurous (A-motility) and social (S-motility) systems. A-motility is used for individual cell gliding, while S-motility is used for gliding in multicellular groups. Video microscopy studies showed that nla24 cells are non-motile on agar surfaces, suggesting that the nla24 gene product is absolutely required for both A-motility and S-motility under these assay conditions. S-motility requires functional type IV pili, wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…M. xanthus strains were grown and development was induced in submerged culture as described previously (29). The procedures for RNA preparation (50), cDNA generation, and QPCR reactions have been described previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…M. xanthus strains were grown and development was induced in submerged culture as described previously (29). The procedures for RNA preparation (50), cDNA generation, and QPCR reactions have been described previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…It was proposed that fibril EPS may mediate the retraction of type IV pili (26), the likely motor for S-motility (38). The regulation of fibril EPS clearly requires multiple genetic loci, including tgl (10), stk (10,22), sglK (40,42), eps and eas (27), nla24 (24), and dif (4,7,45). The dif locus encodes proteins with extensive homology to bacterial chemotaxis proteins.…”
mentioning
confidence: 99%
“…General searches for mutants of M. xanthus with motility defects have shown that single-cell (adventurous, A) motility and group-dependent (social, S) motility are genetically separable and that each type of motility requires the functions of large, nonoverlapping sets of genes (Hodgkin and Kaiser 1979a,b;Macneil et al 1994a,b;Youderian et al 2003). Mutations in only three genes, mglA, which encodes a small GTPase (Stephens and Kaiser 1987;Stephens et al 1989;Hartzell and Kaiser 1991a,b;Hartzell 1997), agmA, which is predicted to encode a critical amidase involved in cell wall biogenesis (Youderian et al 2003), and epsI/nla24, predicted to encode an activator of transcription (Caberoy et al 2003;Lancero et al 2004;Lu et al 2005), have been shown to abolish both mechanisms of motility simultaneously.…”
mentioning
confidence: 99%